The Students’ Perception on the Use of Youtube Videos in English Language Teaching And Learning at Vocational High School - Lastaruli Manurung; Imelda Mallipa; Hengki Mofu (Institut Agama Islam Negeri Palopo, 2023)
The use of YouTube videos in the English teaching process can help students in understanding the teaching materials. However, there are some factors that might affect the successful use of YouTube videos in classroom context. This research was conducted to investigate the students’ perceptions on the use of YouTube videos at SMK Kesehatan Terpadu Manokwari. Thirty-five students in class X Nursing were chosen as participants in this study. The questionnaire was administered to the students to collect the data. The result showed that students have positive perceptions on the use of YouTube videos in the English language teaching and learning process. The process of how the YouTube videos use in the classroom is explained.